Activation of intestinal spinal afferent endings by changes in intra‐mesenteric arterial pressure. (25th June 2015) - Humenick, A.; Chen, B. N.; Wiklendt, L.; Spencer, N. J.; Zagorodnyuk, V. P.; Dinning, P. G.; Costa, M.; Brookes, S. J. H.
Abstract : Key points: A major class of mechano‐nociceptors to the intestine have mechanotransduction sites on extramural and intramural arteries and arterioles ('vascular afferents'). These sensory neurons can be activated by compression or axial stretch of vessels. Using isolated preparations we showed that increasing intra‐arterial pressure, within the physiological range, activated mechano‐nociceptors on vessels in intact mesenteric arcades, but not in isolated arteries. This suggests that distortion of the branching vascular tree is the mechanical adequate stimulus for these sensory neurons, rather than simple distension. The same rises in pressure also activated intestinal peristalsis in a partially capsaicin‐sensitive manner indicating that pressure‐sensitive vascular afferents influence enteric circuits. The results identify the mechanical adequate stimulus for a major class of mechano‐nociceptors with endings on blood vessels supplying the gut wall; these afferents have similar endings to ones supplying other viscera, striated muscle and dural vessels. Abstract: Spinal sensory neurons innervate many large blood vessels throughout the body. Their activation causes the hallmarks of neurogenic inflammation: vasodilatation through the release of the neuropeptide calcitonin gene‐related peptide and plasma extravasation via tachykinins. The same vasodilator afferent neurons show mechanical sensitivity, responding to crushing, compression or axial stretch of blood vessels – responses which activate pain pathways and which can be modified by cell damage and inflammation. In the present study, we tested whether spinal afferent axons ending on branching mesenteric arteries ('vascular afferents') are sensitive to increased intravascular pressure. From a holding pressure of 5 mmHg, distension to 20, 40, 60 or 80 mmHg caused graded, slowly adapting increases in firing of vascular afferents. Many of the same afferent units showed responses to axial stretch, which summed with responses evoked by raised pressure. Many vascular afferents were also sensitive to raised temperature, capsaicin and/or local compression with von Frey hairs. However, responses to raised pressure in single, isolated vessels were negligible, suggesting that the adequate stimulus is distortion of the arterial arcade rather than distension per se . Increasing arterial pressure often triggered peristaltic contractions in the neighbouring segment of intestine, an effect that was mimicked by acute exposure to capsaicin (1 μm ) and which was reduced after desensitisation to capsaicin. These results indicate that sensory fibres with perivascular endings are sensitive to pressure‐induced distortion of branched arteries, in addition to compression and axial stretch, and that they contribute functional inputs to enteric motor circuits.